(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Even though the toponyms in the Baetica come from different languages, they all have a common phonological feature which leads us to think that, before the latinization took place, they had all acquired the features of a previous common language.